Prevalence of depressive symptoms in middle-aged and elderly outpatient patients with chronic pain in three cities and provinces of China - Chengxin Du; Weiwei Zhang; Liyuan Xu; Bifa Fan; Jianqun Dong; Liuxia Yan; Yingying Jiang (Clinical Epidemiology and Global Health)
Background: Chronic pain and depression are closely related, significantly impacting patients' quality of life. Notably, large-scale cross-sectional studies on chronic pain patients are scarce in China. This study examined depressive symptoms' prevalence and factors in three provinces/cities' outpatient patients, aiming to support psychological intervention and diagnostic/treatment services. Methods: Middle-aged and elderly patients with chronic pain in outpatient clinics in China (n = 4151) completed valid questionnaires on demographic characteristics, pain status, and depression in a cross-sectional study design. The chi-square test was used for comparison between groups, and multivariate logistic regression was used to analyze the influencing factors of depression in middle-aged and elderly patients with chronic pain. Results: Among 4151 patients with chronic pain, 9.1 % had depression symptoms. The prevalence of depressive symptoms in patients with severe pain was 24.2 %. As the severity of pain increased, the detection rate of depressive symptoms showed an upward trend (trend test x2 = 165.156, P < 0.001). Past medical history (OR = 1.83, 95%CI: 1.28–2.62), insomnia (OR = 2.58, 95%CI: 2.03–3.29), number of pain sites ≥2 (OR = 1.60, 95%CI: 1.27–2.03), and severe pain (OR = 3.54, 95%CI: 2.28–5.51), dissatisfaction pain treatment (OR = 2.50, 95%CI: 1.83–3.42) were risk factors for depressive symptoms. Conclusions: As the severity of pain increased, the detection rate of depressive symptoms showed an upward trend. Psychological health prevention and intervention should be actively implemented in key populations of chronic pain patients to improve the effectiveness and satisfaction of pain treatment.